Coevolutionary history of predation constrains the evolvability of antibiotic resistance in prey bacteria - Saheli Saha; Sneha Sureshkumar; Vaibhav Sharma; Samay Pande (npj Antimicrobials and Resistance)
Abstract Understanding how the historical contingency of biotic interactions shapes the evolvability of bacterial populations is imperative for the predictability of the eco-evolutionary dynamics of microbial communities. While microbial predators like Myxococcus xanthus influence the frequency of antibiotic-resistant bacteria in nature, the effect of adaptation to the presence of predators on the evolvability of prey bacteria to future stressors is unclear. Hence, to understand the influence of the coevolutionary history of predation on the evolvability of antibiotic resistance, we propagated variants of E. coli, pre-adapted to distinct biotic and abiotic conditions, in gradually increasing concentrations of antibiotics. We show that pre-adaptation to predators limits the evolution of a high degree of antibiotic resistance. Moreover, lower degree of resistance in the evolved strains also incurs reduced fitness costs while preserving their ancestral ability to resist predation. Together, we demonstrate that the history of biotic interactions can strongly influence the evolvability of bacteria.